MANFAAT DAN PENGORBANAN SUMBERDAYA SEBAGAI PEMBENTUKAN NILAI KONSUMEN - Agus Hasan Pura A (Bina Ekonomi, 2013)
The difference between total perceived benefits and cost provides a measure of perceived customer value. The larger the customer value, the greater is the potential to attract, satisfy and retain customers. Customer analysis and value creation are important inputs in developing marketing strategies designed to yield high levels of customer satisfaction.